Correlation of the triglyceride-glucose-body mass index with all-cause and cardiovascular mortality in patients undergoing peritoneal dialysis: a retrospective cohort study - Li, Jinping; Wang, Xichao; Zhang, Wenyu; Sun, Na; Han, Yingying; Chang, Wenxiu (Frontiers in Nutrition, 2025)
BackgroundThe triglyceride-glucose-body mass index (TyG–BMI) is a simple indicator of insulin resistance and is linked to an elevated risk of mortality. Nevertheless, limited research has explored the associations between the TyG–BMI and all-cause and cardiovascular mortality in patients undergoing peritoneal dialysis (PD).MethodsPatients initiating PD treatment at the Tianjin First Central Hospital’s Nephrology Department from July 2013 to February 2024 had triglycerides, fasting blood glucose, height, and weight measured at baseline and monthly during follow-up. TyG–BMI was calculated, dividing PD patients into high, middle, or low TyG–BMI groups using the tri-quantile method. Cox regression analysis assessed hazard ratios (HRs) for all-cause and cardiovascular mortality among these groups. A restricted cubic spline regression was used to explore the relationship between TyG–BMI and the primary and secondary outcomes.ResultsA total of 865 patients were included. The mean TyG–BMI value for the entire study population was 212.27 ± 46.64. Patients in the high TyG–BMI group had a higher proportion of patients whose primary kidney disease was diabetic nephropathy and the greatest proportion of patients with comorbid diabetes mellitus. During the follow-up, 266 (30.75%) deaths occurred, with CVD being the dominant cause in 110 (41.35%) patients. Univariate and multivariate Cox regression analyses showed that middle group patients had a significantly lower risk of all-cause mortality compared to other groups. For CVD mortality, high group patients had a significantly greater hazard ratio than middle group patients, while there was no significant difference between the low and middle groups. Restricted cubic spline regression revealed a U-shaped association between TyG–BMI and all-cause mortality risk, as well as a J-shaped association with CVD mortality; inflection points were identified at 209.73 and 206.64, respectively. In the subgroup analysis, we found that higher TyG–BMI values were associated with increased all-cause and cardiovascular mortality in men, and lower TyG–BMI values were linked to elevated all-cause mortality in women.ConclusionThe TyG–BMI shows U-shaped and J-shaped relationships with all-cause and CVD mortality risk, respectively, in PD patients. Additionally, significant sex differences were observed in these associations.